2016
DOI: 10.1055/s-0036-1593805
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Exoskeletons as Assistive and Rehabilitation Devices in the Treatment of Neurologic Gait Disorders in Patients with Spinal Cord Injury: A Systematic Review

Abstract: Study Design Systematic review. Clinical Questions (1) When used as an assistive device, do wearable exoskeletons improve lower extremity function or gait compared with knee-ankle-foot orthoses (KAFOs) in patients with complete or incomplete spinal cord injury? (2) When used as a rehabilitation device, do wearable exoskeletons improve lower extremity function or gait compared with other rehabilitation strategies in patients with complete or incomplete spinal cord injury? (3) When used as an assistive or rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 46 publications
(103 reference statements)
2
40
0
2
Order By: Relevance
“…Morganti et al [12] showed a significant positive correlation between the WISCI and SCIM (r=0.97, p<0.001).…”
Section: Requirements For Functional Walkingmentioning
confidence: 91%
See 4 more Smart Citations
“…Morganti et al [12] showed a significant positive correlation between the WISCI and SCIM (r=0.97, p<0.001).…”
Section: Requirements For Functional Walkingmentioning
confidence: 91%
“…This way, the patient's voluntary drive is integrated in the walking pattern. This mechanism could lead to neuronal plasticity and possibly result in increased mobility even when not wearing the exoskeleton [12].…”
Section: Exoskeletonsmentioning
confidence: 99%
See 3 more Smart Citations